(untitled) (Communications in Computational Physics, 2025)
This study systematically investigates the flow characteristics around an inclined rounded square cylinder in the laminar flow regime, focusing on key influential parameters. The simulations cover a broad parameter space, including incidence angles from 0^◦ to 45^◦, Reynolds numbers from 45 to 170, and corner radii from 0 to 0.4. Data from direct numerical simulations, including mean force and moment coefficients, root mean square of force fluctuation coefficients, and Strouhal numbers, are meticulously analyzed and divided into two datasets for model training. The developed data-driven model exhibits exceptional predictive accuracy, mirroring a high-fidelity physical model. Based on this model, the optimization strategy also demonstrates notable accuracy. Specifically, the implementation of optimal design using the high-fidelity model allows precise control of output physical parameters, aligning them with targeted optimal conditions. This capability offers significant potential for improving the efficiency of various engineering applications.